The Effect of Age on Second Language Acquisition (B2) in Children Aged 9-12 Years - Pawi, Muzamil R; Nadzifah, Wahdah Wulidatus Sofrotun; Fikri, Shofil; Aisy, Fiqi Rihadatul (Jurnal Al Burhan, 2025)
Childhood is considered the optimal period due to the brain's flexibility, which enhances the ability to learn new languages. This study specifically focuses on the age factor in second language learning and aims to prove the assumption that a child's critical age correlates with their language acquisition ability. This is a quantitative study with a descriptive approach, using data processing software, SPSS, and subsequently described verbally. The sampling technique employed was purposive sampling, resulting in a sample of 21 students from Ulya classes 1 and 2 at TPQ Darut Tarbiyah As-Sa'adah, comprising 17 female students and four male students. The results of the product-moment calculation showed that the calculated r-value was lower than the table r-value, specifically 0.433 < 0.829. This indicates no influence between the variables of age and language acquisition. Therefore, age does not affect a child's ability to acquire a second language among students in Ulya classes 1 and 2 at TPQ Darut Tarbiyah As-Sa’adah for the 2024/2025 academic year.